Minimisation of Fermentation Period of Shidal from Barbs (Puntius spp.) - Muzaddadi, Armaan Ullah (Fishery Technology, 2025)
Fermented barb (Puntius spp.) is a semi-fermented solid fish product of north-east India which is a popular means of fish preservation and product development in the region. Its normal fermentation period is 4-6 months which restricts the production only to 2 batches per year. In the present study, fortnightly samples from traditional shidal fermenting vessels (mutka) (PC) and laboratory prepared shidal (L) were analyzed to identify an appropriate stage and time of fermentation for harvesting shidal with desired quality. A total of 5 fermentation stages were characterized. Bacillus, Staphylococcus and Micrococcus were the predominant genera of bacteria. Biochemical parameters such as pH, titratable acidity and proximate composition combined with sensory analysis suggested that good quality shidal can be harvested after a fermentation period of 75 days (stage 3) under traditional fermentation system at room temperature (30Â±5oC) and from this stage onwards the quality of shidal was best at 120 days of fermentation with highest sensory scores, dark red brown colour, typical shidal odour, pH 5.7Â±0.8 and titratable acid 1.78%. Shidal had excellent nutritional properties including 33- 34% moisture, 30-31% protein, about 18-19% fat and 11-13% ash content.